Analysis of total harmonic distortion and switching losses of PWM in grid-connected photovoltaic system - Syahierah Eliya, Sabri (2019)
Photovoltaic (PV) system becomes the best alternative energy choice to produce electricity that can replace fuel resource and at the same time not harmful to our environment. Grid-connected PV (GCPV) system supply the AC power generated to the utility grid then distributed to the consumer. In a GCPV system, an inverter is a mandatory, but it is a non-linear load that generates more total harmonic distortion (THD) into the electrical power system. Harmonic generated by the PV system may downgrade the quality of power grid and affect the reliability and safety. IEEE Std 519- 1992 and the largest Malaysia electricity utility company Tenaga Nasional Berhad (TNB) standard stated that, THD should be less than 5 % in the rated inverter output of the cable connected to Points of Common Coupling (PCC). Moreover, the solar irradiance in Malaysia varies daily and also throughout the year. The consequence of low irradiance level is that the output of the PV array is low and thus the input of the inverter relatively becoming low. The inverter exhibit large non-linearity when the inverter is operating at low power input during the low level of solar irradiance. The THD in a GCPV system is influenced by the solar irradiance due to the inversely proportional relationship between solar irradiance and THD. In addition, other main concerns in the GCPV system are switching losses of the switching devices in the inverter. The effectiveness of a system can improve by keeping the switching losses as low as possible. Pulse Width Modulation (PWM) techniques has its own benefits such as easy to implement and control, compatible with today’s digital microprocessor, no additional components needs to be added to obtain control of the output voltage and lastly, lower harmonics can be eliminated or minimized. In this research, the main objective is to carry out research to minimize harmonics and switching loss reduction in the GCPV system. A GCPV system model in MATLAB/Simulink is used as the platform to implement continuous PWM (CPWM) and discontinuous PWM (DPWM) in the inverter control to investigate the effect of PWM switching frequency selection on THD and switching losses performance at different level of solar irradiance. The techniques were compared and CPWM is suggested as the recommended solution. This is due to the lower THD value obtained when CPWM applied in the inverter control. Additionally, the THD when DPWM applied is higher compared to CPWM at all solar irradiance levels. The appropriate minimum switching frequency of the PWM at different solar irradiance level that meet the standard THD requirement with minimum switching losses is proposed in this thesis. The appropriate switching frequency value for each of the solar irradiance ranges are fsw1 = 12600.00 Hz during 200 – 400 W/m², f sw2 = 5000.00 Hz when 401 – 600 W/m², fsw3= 1746.00 Hz throughout 601 – 800 W/m² and f sw4 = 1545.50 Hz for 801 – 1000 W/m² solar irradiance level. Meanwhile, DPWM required higher switching frequency to meet the standard THD and thus lead to higher switching losses in the system. The key finding in this investigation is the appropriate selection of switching frequency of the PWM may decrease the THD content at different solar irradiance level